Organic phase separation opens up new opportunities to interrogate the RNA-binding proteome - Smith, Tom; Villanueva, Eneko; Queiroz, Rayner M. L.; Dawson, Charlotte S.; Elzek, Mohamed; Urdaneta Zurbarán, Erika Cristina; Willis, Anne E.; Beckmann, Benedikt M.; Krijgsveld, Jeroen; Lilley, Kathryn S. (Current opinion in chemical biology, 2020)
Protein-RNA interactions regulate all aspects of RNA metabolism and are crucial to the function of catalytic ribonucleoproteins. Until recently, the available technologies to capture RNA-bound proteins have been biased toward poly(A) RNA-binding proteins (RBPs) or involve molecular labeling, limiting their application. With the advent of organic-aqueous phase separation-based methods, we now have technologies that efficiently enrich the complete suite of RBPs and enable quantification of RBP dynamics. These flexible approaches to study RBPs and their bound RNA open up new research avenues for systems-level interrogation of protein-RNA interactions.